The Retina in Patients With Triple A Syndrome: A Window Into Neurodegeneration? - Ulgiati, Fiorenza; Lhoir, Sophie; Balikova, Irina; Tenoutasse, Sylvie; Boros, Emese; Vilain, Catheline; Heinrichs, Claudine; Brachet, Cécile (Frontiers in Endocrinology, 2021)
Objective Experimental evidence suggests that the clinical manifestations of Triple A syndrome result from oxidative stress. Several conditions caused by oxidative stress display retinal involvement. Our objective was to assess the retina and optic nerve involvement in children with Triple A syndrome. Methods Eleven patients with genetically proven Triple A syndrome followed-up in our centre were approached for study participation. The main outcome was the measurement of the thicknesses of the different retinal layers by Optical Coherence Tomography (OCT). Results 9 patients with triple A syndrome had OCT measurements. 7 patients were children and 2 were adults; 4 were females and 5 were males. The 7 paediatric patients had at least two OCT measured at a mean interval of 7.9 months after the first one. The average Retinal Nerve Fibre Layer thickness was 74 ± 10 µm in patients compared to the paediatric reference range of 100 ± 2 µm (p<0.05). Conclusions and Relevance This is the first study to document retinal layer thicknesses in a series of patients with Triple A syndrome. Nearly all retinal thickness and peripapillary RNFL measurements were very significantly inferior to the reference range in Triple A patients, whatever their age. RNFL thinning was more marked at the temporal part of the optic nerve. OCT being non-invasive, it represents a promising tool to assess the severity of neurodegeneration in patients with Triple A syndrome.